Knowledge, attitude and practice of medical ethics among medical intern students in a Medical College in Kathmandu - Aacharya, Ramesh P; Shakya, Yagya L (Bangladesh Journal of Bioethics, 2015)
This baseline study was conducted to find out the knowledge, attitudes and practices of medical ethics among the undergraduate medical interns who did not have structured ethics curriculum in their course. A descriptive, cross-sectional study was carried out using a self-administered structured questionnaire among the medical undergraduate interns of Maharajgunj Medical Campus, the pioneer medical college of Nepal which enrols 60 students in a year. A total of 46 interns participated in the study. The most common source of knowledge on ethics was lectures/seminars (35.7%) followed by experience at work (24.5%), training (21.4%) and own reading (17.3%). The main contents of Hippocratic Oath were known to 98.8% while 60.9% knew the main contents of Nepal Medical Council (NMC) code of ethics. Great majority (91.3%) regard ethics as very important in medical profession. Doctors know the best irrespective of patients opinion was disagreed by only 39.1% indicating the paternalistic attitude. However, 78.3% were in favour of adhering to the patients wish. None of the participant agreed to abandon confidentiality. Only about one-fourth (26.1%) claim to encounter ethical dilemma every day while the highest number (43.5%) had once in a month. To deal with the situation of ethical dilemma, majority approached to immediate supervisor followed by head of the department and colleagues. Eighty-seven percent of participating interns were involved in research activities involving human subjects. Only one of the participants had encountered the ethical issue on end-of-life and it was do-not-resuscitate consent in a terminally ill patient. On implementation of the curriculum on medical ethics focus should be - principles of biomedical ethics, sensitive ethical dilemmas like end-of-life care and practical experiences with participation in deliberations of the ethics committee.